2018
DOI: 10.3389/fnins.2018.00648
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of PEDOT:PSS/Alginate Soft Microelectrodes for Application in Neuroprosthetics

Abstract: Reducing the mechanical mismatch between the stiffness of a neural implant and the softness of the neural tissue is still an open challenge in neuroprosthetics. The emergence of conductive hydrogels in the last few years has considerably widened the spectrum of possibilities to tackle this issue. Nevertheless, despite the advancements in this field, further improvements in the fabrication of conductive hydrogel-based electrodes are still required. In this work, we report the fabrication of a conductive hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…This method creates a three-dimensional analog of the two-dimensional electrode surface. These coatings are collectively referred to as hydrogel polymer coatings, with PEDOT:PSS as the most well-known of these (Nyberg et al, 2002; Ferlauto et al, 2018). These polymers conduct electronic current and have the property of absorbing the surrounding electrolyte (e.g., body fluid) that allows for a capacitive interface between ions and electrons to form on a molecular scale throughout the polymer chains.…”
Section: Enabling Technologymentioning
confidence: 99%
“…This method creates a three-dimensional analog of the two-dimensional electrode surface. These coatings are collectively referred to as hydrogel polymer coatings, with PEDOT:PSS as the most well-known of these (Nyberg et al, 2002; Ferlauto et al, 2018). These polymers conduct electronic current and have the property of absorbing the surrounding electrolyte (e.g., body fluid) that allows for a capacitive interface between ions and electrons to form on a molecular scale throughout the polymer chains.…”
Section: Enabling Technologymentioning
confidence: 99%
“…CPH have been suggested as suitable candidates for interfacial modification since they can combine both electrochemical and biochemical qualities in one material . In recent years, a wide range of different CPHs have been suggested as interesting candidates for neural probes and many studies have investigated the micropatterning of CPHs, for example, via photolithography, inkjet printing, mold casting, or electrodeposition . Alternatively, it is possible to coat the entire device with the hydrogel and subsequently deposit the conducting polymer into the hydrogel matrix, so that a conducting network is formed at the electrode surfaces only .…”
Section: Discussionmentioning
confidence: 99%
“…In an ideal scenario, the CPH can then be coated onto selected electrode sites, for example, as a drug‐release system, while other electrodes remain available for alternative functionalizations. A possible method for micropatterning CPHs, based on a phytic acid gelated polyaniline hydrogel by inkjet printing or spray coating, has been reported by Pan et al Other reported techniques include mold casting, photolithography, or electrodeposition . Several CPHs used for neural interfaces are based on dip coating the hydrogel onto the entire surface of the device followed by the deposition of the CP selectively at the electrode site .…”
Section: Introductionmentioning
confidence: 99%
“…Impedance spectroscopy was performed between 10 Hz and 1 MHz with an AC voltage of 50 mV. CV was obtained by sweeping a cyclic potential at a speed of 50 mV s −1 between −0.6 and 0.8 V. For each electrode, the average response over five cycles was calculated …”
Section: Methodsmentioning
confidence: 99%